The expert learner challenging the myth of ability - Stobart, Gordon (Maidenhead, Berkshire, England Open University Press, 2014)
This book looks at what we know about becoming a skilled performer or practitioner and how this relates to classroom teaching and learning.
Keywords: Learning ability; Learning; Teaching